2014
DOI: 10.1007/s10086-014-1417-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of lignin and lignin precursors in differentiating xylem of Japanese cypress and poplar

Abstract: Lignin is an integral component of the cell wall of vascular plants. The mechanism of supply of lignin precursors from the cytosol into the cell wall of differentiating xylem has not yet been elucidated. The present study showed that a certain amount of coniferyl alcohol glucoside (coniferin) occurred in the differentiating xylem of Japanese cypress (Chamaecyparis obtusa), as previously reported in gymnosperms. Coniferin content peaked in the early stages of secondary wall formation and decreased during lignif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…A knowledge of the distribution of lignin and lignin precursors may provide insights into the lignification mechanism, including the transport step. Several studies have elucidated the distribution of lignin and coniferin, the glucoside of coniferyl alcohol, in differentiating xylem of gymnosperm [15][16][17]. Lignification and the occurrence of lignin precursors have been examined in the angiosperms Magnolia kobus [18] and poplar [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A knowledge of the distribution of lignin and lignin precursors may provide insights into the lignification mechanism, including the transport step. Several studies have elucidated the distribution of lignin and coniferin, the glucoside of coniferyl alcohol, in differentiating xylem of gymnosperm [15][16][17]. Lignification and the occurrence of lignin precursors have been examined in the angiosperms Magnolia kobus [18] and poplar [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have elucidated the distribution of lignin and coniferin, the glucoside of coniferyl alcohol, in differentiating xylem of gymnosperm [15][16][17]. Lignification and the occurrence of lignin precursors have been examined in the angiosperms Magnolia kobus [18] and poplar [16]. The results of those studies suggested that the lignin precursors are coniferin in gymnosperms and M. kobus, and sinapyl alcohol in poplar.…”
Section: Introductionmentioning
confidence: 99%
“…There are three important pieces of information known about coniferin transport. First, compound 1D is found in the cambial sap of many tree species [1,5]. Second, coniferin β-glucosidase is located in the cell wall of coniferous and broad-leaf trees [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The pool size is large enough to allow its isolation in most gymnosperms and magnolia that emerged in an early stage of phylogeny (Soltis et al 1999). The pool size is small in most angiosperm trees such as cherry, oak, and poplar (Terazawa et al 1984;Tsuyama and Takabe 2014).…”
Section: Pool Size Of Mlgs As Intermediates In Lignin Biosynthesismentioning
confidence: 99%